How COVID-19 has affected general practice consultations and income: general practitioner cross-sectional population survey evidence from Ireland. Issue 4 (8th April 2021) - Homeniuk, Robyn; Collins, Claire
Abstract : Objectives: How general practice is delivered in many countries has drastically changed due to the COVID-19 pandemic. This study aimed to answer the question of how general practice has changed in Ireland in response to COVID-19. Design: The Irish College of General Practitioners surveyed its membership before and after the global pandemic hit Ireland using a cross-sectional online survey instrument. Setting: This study focuses on primary care, specifically general practice, in Ireland. Participants: In February 2020 before the global pandemic, 526 general practices across Ireland submitted responses to the survey; 538 general practices responded to the second survey during the pandemic in June 2020. This covers 32% and 33% of practices in Ireland, respectively. Main outcome measures: The type of consultations by general practitioners (GPs) and practice nurses in both surveys is the main outcome measure reported in this paper. Other changes such as the perceived change in attendance by certain patient groups and practice income are also reported. Results: Face-to-face consultations significantly (p<0.001) decreased from a median of 26 (IQR 21.3–30) to a median of 8 (IQR 6–13). GP telemedicine consultations increased (p<0.001) from a median of 2.4 (IQR 0–5.3) to a median of 11.3 (IQR 6–19). The majority of practices (80.0%) reported reduced practice profit. Respondents reported a decline in non-COVID-19-related consultations among certain patient cohorts—92.0% for children under 6 years old; 79.5% for patients over 70 years. Conclusions: It is likely that the way general practice is delivered will not return to as it was before the COVID-19 pandemic and increased telemedicine can be expected. However, it is necessary to assess the impact of this shift on patient health and to assess healthcare provider and patient experience to ensure continued high-quality care and patient safety.